Damascene Process Development for Low-Loss Photonics Devices with Applications in Frequency Comb - Qiaoling Zhou; Yejia Jin; Shaonan Zheng; Xingyan Zhao; Yang Qiu; Lianxi Jia; Yuan Dong; Qize Zhong; Ting Hu (Photonics, 2024)
Silicon nitride (SiN) is emerging as a material of choice for photonic integrated circuits (PICs) due to its ultralow optical losses, absence of two-photon absorption in telecommunication bands, strong Kerr nonlinearity and high-power handling capability. These properties make SiN particularly well-suited for applications such as delay lines, chip-scale frequency combs and narrow-linewidth lasers, especially when implemented with thick SiN waveguides, which is achieved through low-pressure chemical vapor deposition (LPCVD). However, a significant challenge arises when the LPCVD SiN film thickness exceeds 300 nm on an 8-inch wafer, as this can result in cracking due to high stress. In this work, we successfully develop a damascene process to fabricate 800 nm-thick SiN photonics devices on an 8-inch wafer in a pilot line, overcoming cracking challenges. The resulting 2 × 2 multimode interference (MMI) coupler exhibits low excess loss (−0.1 dB) and imbalance (0.06 dB) at the wavelength of 1310 nm. Furthermore, the dispersion-engineered SiN micro-ring resonator exhibits a quality (Q) factor exceeding 1 × 106, enabling the generation of optical frequency combs. Our demonstration of photonics devices utilizing the photonics damascene process sets the stage for high-volume manufacturing and widespread deployment.